Trends in Karyotype Evolution in Astyanax (Teleostei, Characiformes, Characidae): Insights From Molecular Data - Pazza, Rubens; Dergam, Jorge A.; Kavalco, Karine F. (Frontiers in Genetics, 2018)
The study of patterns and evolutionary processes in Neotropical fish is not always an easy task due the wide distribution of major fish groups in large and extensive river basins. Thus, it is not always possible to delineate the effects of chromosome rearrangements in the evolution of biodiversity. In the Astyanax genus, chromosome data obtained since the 1970s have shown evidence of cryptic species, karyotypic plasticity, supernumerary chromosomes, triploidies and minor chromosomal rearrangements. In the present work we map and discuss the main chromosomal events in relation to the molecular evolution of the genus Astyanax (Characiformes, Characidae) using mitochondrial DNA sequence data, in the search for major chromosome evolutionary trends within this taxon.